2022
DOI: 10.3390/ijms232214101
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase-4 Inhibitor-Related Bullous Pemphigoid: Clinical, Laboratory, and Histological Features, and Possible Pathogenesis

Abstract: Dipeptidyl peptidase-4 inhibitor (DPP4i) is a widely used antidiabetic agent. Emerging cases of DPP4i-associated bullous pemphigoid (DBP), whose pathogenesis remains unclear, have been reported. Thus, a retrospective study was conducted from January 2016 to June 2021 to determine the clinical, laboratory, and histopathological features of DBP and idiopathic bullous pemphigoid (IBP). We set up in vitro experiments using vildagliptin-treated HaCaT keratinocytes to validate what we found by analyzing published RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 57 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…DPP-4i-associated bullous pemphigoid (BP) manifests a non-inflammatory phenotype, with a predominance of blisters and less erythema than idiopathic BP. 10 On histopathology, the number of infiltrating eosinophils was lower in DPP-4i-associated BP than in idiopathic BP. 10 It has been reported that the expression of LAMA3, LAMB3, LAMC2 encoding laminin-332, and COL17A1 encoding BP180 (which are related to the dermal-epidermal junction) was decreased in DPP-4i treated keratinocytes.…”
Section: Dear Editorsmentioning
confidence: 91%
See 2 more Smart Citations
“…DPP-4i-associated bullous pemphigoid (BP) manifests a non-inflammatory phenotype, with a predominance of blisters and less erythema than idiopathic BP. 10 On histopathology, the number of infiltrating eosinophils was lower in DPP-4i-associated BP than in idiopathic BP. 10 It has been reported that the expression of LAMA3, LAMB3, LAMC2 encoding laminin-332, and COL17A1 encoding BP180 (which are related to the dermal-epidermal junction) was decreased in DPP-4i treated keratinocytes.…”
Section: Dear Editorsmentioning
confidence: 91%
“…10 On histopathology, the number of infiltrating eosinophils was lower in DPP-4i-associated BP than in idiopathic BP. 10 It has been reported that the expression of LAMA3, LAMB3, LAMC2 encoding laminin-332, and COL17A1 encoding BP180 (which are related to the dermal-epidermal junction) was decreased in DPP-4i treated keratinocytes. 10 Therefore, DPP-4i treatment may cause fragility of the dermal-epidermal junction, leading to DPP-4i-associated BP with a non-inflammatory phenotype.…”
Section: Dear Editorsmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, a retrospective study on BP patients revealed that the total number of eosinophils infiltrating the skin was considerably lower in DBP patients compared to idiopathic BP patients [53]. Authors found that vildagliptin could also have immunomodulatory functions via regulating IL‐6 production in DBP pathogenesis [54]. It is speculated that suppression of DPP‐4/CD26 may be involved in the disruption of BP180, major BP autoantigen, immunotolerance, and the subsequent development of epitopes for BP autoantibodies [55].…”
Section: Effects Of Dpp‐4 Inhibitors In Therapy Beyond Glucose Controlmentioning
confidence: 99%
“…Interestingly, Hung et al recently reported that vildagliptin can stimulate the expression of IL-6 by keratinocytes in vitro, subsequently increasing its levels through a positive feedback loop. As a result, keratinocytes treated with DPP4i may supply sufficient IL-6 in the skin of DPP4i-BP patients, even if eosinophils and other inflammatory cells are reduced [105].…”
Section: Currently Described Immune and Pathogenic Mechanismsmentioning
confidence: 99%